Relación del sector turismo en el comportamiento de la pobreza en Cartagena durante el periodo 2010-2020 (2023)
The tourism sector in Cartagena is known as being one of the most important for the economic activity of the city, since having places with high flows of people who daily enter and leave the city, are in charge of generating income for the families that depend on it, since in the derivations of tourism there are different establishments that are in charge of welcoming tourists and offering different services such as lodging, transportation, food and entertainment, which are also strategically distributed throughout the city. , and with this brings the relationship with the levels of poverty, since there is a particularity in the city in which Cartagena is located among the cities with the most inequality in the city both in monetary, multidimensional poverty indices, Gini coefficient and Needs Unsatisfied basics, which seems unusual for a city with such strong economic activity, not only at the Cartagena level but also at the national level.